Sex ratio among offspring of childhood cancer survivors treated with radiotherapy - Winther, J F (Nature Publishing Group, 2003)
It has been postulated that paternal gonadal exposure would increase the sex ratio by inducing X-chromosomal dominant lethals but that maternal gonadal exposure would decrease the sex ratio by inducing recessive sex-linked lethals. We therefore evaluated the sex ratio (male-to-female ratio) of children born to survivors of childhood cancers in Denmark. Children with cancer were identified from the Danish Cancer Registry from 1943 to 1996 and their offspring from the Central Population Registry. Radiation treatments were determined from records within the Cancer Registry and gonadal radiation exposures were estimated based on the cancer being treated and the likely proximity of the radiation fields to the gonads. Overall, 1100 survivors of childhood cancer became the parents of 2130 children. The sex ratio for male (0.99) and female (1.00) cancer survivors was similar and did not differ significantly from the Danish population (1.06). Radiotherapy did not influence the sex ratio of the children of either male or female survivors, and there was no evidence for dose-related changes over categories of estimated dose to parental gonads. We saw no consistent association between the sex ratio and the interval between cancer diagnosis of the parent and birth of the child. This nationwide study provides no support for the hypothesis that radiation exposure to the gonads results in an inherited genetic effect that would be manifested by a change in the sex ratio of children born after exposure. It may be, however, that sex ratio alterations are not a good or even a valid indicator of possible genetic effects in humans.